Spectral characteristic of fluorescence induction in a model cyanobacterium, Synechococcus sp. (PCC 7942) - Kana, Radek; Prásil, Ondrej; Komárek, Ondrej; Papageorgiou, George C; Govindjee (Biochimica et biophysica acta, 2009)
We present here three-dimensional time-wavelength-intensity displays of changes in variable fluorescence, during the O(JI)PSMT transient, observed in cyanobacterium at room temperature. We were able to measure contributions of individual chromophores to fluorescence spectra at various times of fluorescence induction (FI). The method was applied to a freshwater cyanobacterium, Synechococcus sp. (PCC 7942). Analysis of our experimental results provides the following new conclusions: (i) the main chlorophyll (Chl) a emission band at approximately 685 nm that originates in Photosystem (PS) II exhibits typical fast (OPS) and slow (SMT) FI kinetics with both orange (622 nm) and blue (464 nm) excitation. (ii) Similar kinetics are exhibited for its far-red emission satellite band centered at approximately 745 nm, where the PS II contribution predominates. (iii) A significant OPS-SMT-type kinetics of C-phycocyanin emission at approximately 650 nm are observed with the blue light excitation, but not with orange light excitation where the signal rose only slightly to a maximum. The induction of F650 was not caused by an admixture of the F685 fluorescence and thus our data show light-inducible and dark-reversible changes of phycobilin fluorescence in vivo. We discuss possible interpretations of this new observation.
Keywords: časové faktory; absorpce; Light; fluorescenční spektrometrie; Models, Biological; Spectrometry, Fluorescence; Kinetics; Absorption; Synechococcus; světlo; Time Factors; kinetika; biologické modely